“CLASPing” tungsten's effects on microtubules with “PINs” - Adamakis, Ioannis Dimosthenis S (Plant Signal Behav, 2015)
Tungsten, supplied as sodium tungstate, inhibits root elongation in Arabidopsis thaliana, which has been attributed to a diminishing of PIN2 and PIN3 auxin efflux carriers. In this work, we sought to analyze the effect of tungsten on cortical microtubules and CLASP (Cytoplasmic Linker Associated Protein), which are also involved in the anisotropic cell expansion of root cells. Seedlings grown in a tungsten-free substrate for 4 d and then transplanted into a tungsten-containing substrate exhibited randomly oriented microtubules in a time-dependent manner. While tungsten had no effect on roots treated for 3 h, microtubule alignment was obviously affected in the transition and elongation zones after a 6, 12, 24, 48 h tungsten treatment, at prolonged tungsten administrations and in seedlings grown directly in the presence of tungsten. This change in microtubule orientation may be associated with the reduction of CLASP protein expression induced by tungsten, as evidenced in experiments with plants expressing the CLASP-GFP protein. A possible mechanism, by which the coordinated functions of CLASP, PIN2 and microtubules are affected, as revealed by inhibited root growth, is discussed.